pls (−42) + 27 =
(−2) ⋅ 3 − 56 :(−8) =
(−2) ⋅ (−7) =
(−27) − (−35) =
(−6) ⋅ 4 =
36 :(−6) ⋅ (−3) =
(−14) + (−76) =
72 :(−8) =
7⋅(−12) - (−16) + (-12) : (-3)
(−12) − 39 =
38 + (−15) =
(−63) :(−9) =
34 − 47 =
1 - 2 + 3 - 4 +5 - 6 + 7 - 8 + ........... -98 + 99 - 100 =



Odpowiedź :

(−42) + 27 = - 15

(−2) ⋅ 3 − 56 :(−8) = - 6 - (-7) = 1

(−2) ⋅ (−7) = 14

(−27) − (−35) = - 27 + 35 = 8

(−6) ⋅ 4 = - 24

36 :(−6) ⋅ (−3) = - 6 * (-3) = 18

(−14) + (−76) = - 90

72 :(−8) = - 9

7⋅(−12) - (−16) + (-12) : (-3) = - 84 - (-16) + 4 = 84 + 16 + 4 = 104

(−12) − 39 = - 51

38 + (−15) = 18

(−63) :(−9) = 7

34 − 47 = - 13